Evolution of a Short and Stereocontrolled Synthesis of (+)-7,20-Diisocyanoadociane - Roosen, Philipp C.; Karns, Alexander S.; Ellis, Bryan D.; Vanderwal, Christopher D. (Journal of organic chemistry, 2022)
A full account of the development of a concise and highly stereoselective synthesis of (+)-7,20-diisocyanoadociane (DICA)-a structurally complex isocyanoditerpene with potent antiplasmodial activity-is described. The strategy that evolved relies on the rapid construction of unsaturated tricyclic precursors designed to undergo stereocontrolled Birch reductions and a subsequent bay ring formation to generate the isocycloamphilectane core. This report is divided into three sections: (1) a description of the initial strategy and the results that focused our efforts on a single route to the DICA core, (2) a discussion of the precise choreography needed to enable a first-generation formal synthesis of (+/-)-DICA, and (3) the execution of a 13-step second-generation synthesis of (+)-DICA that builds on important lessons learned from the first-generation effort.